Artificial intelligence‐based computer vision in surgery: Recent advances and future perspectives. Issue 1 (8th October 2021) - Kitaguchi, Daichi; Takeshita, Nobuyoshi; Hasegawa, Hiro; Ito, Masaaki
Abstract: Technology has advanced surgery, especially minimally invasive surgery (MIS), including laparoscopic surgery and robotic surgery. It has led to an increase in the number of technologies in the operating room. They can provide further information about a surgical procedure, e.g. instrument usage and trajectories. Among these surgery‐related technologies, the amount of information extracted from a surgical video captured by an endoscope is especially great. Therefore, the automation of data analysis is essential in surgery to reduce the complexity of the data while maximizing its utility to enable new opportunities for research and development. Computer vision (CV) is the field of study that deals with how computers can understand digital images or videos and seeks to automate tasks that can be performed by the human visual system. Because this field deals with all the processes of real‐world information acquisition by computers, the terminology "CV" is extensive, and ranges from hardware for image sensing to AI‐based image recognition. AI‐based image recognition for simple tasks, such as recognizing snapshots, has advanced and is comparable to humans in recent years. Although surgical video recognition is a more complex and challenging task, if we can effectively apply it to MIS, it leads to future surgical advancements, such as intraoperative decision‐making support and image navigation surgery. Ultimately, automated surgery might be realized. In this article, we summarize the recent advances and future perspectives of AI‐related research and development in the field of surgery. Abstract : In recent years, image recognition by artificial intelligence (AI) has advanced to the point where it is comparable to that of humans. If AI‐based image recognition technology can be effectively applied to surgery, it will lead to the realization of future surgical advancements, such as intraoperative decision‐making support, image navigation surgery, and automated surgery. In this article, the recent advances and future perspectives of AI‐related research and development in the field of surgery are summarized.